Good Governance for Food Security in Bangladesh: Exploring the Role of Administration and Stakeholders in Policy Decision-Making - Rajib Chandra Das; Sajib Mondol; Abu Musa (Review of Human Resources, Organizational Change, and Economic Impact, 2025)
Food security in Bangladesh is a major issue that addresses both social and economic factors. The present study was conducted to identify and overcome the challenges of good governance in ensuring safe food in Bangladesh. In recent years, some positive initiatives have been taken by government and private initiatives to ensure safe food but despite this, there has been no effective and permanent progress in ensuring safe food. The results of this study show that the initiatives taken at the practical level are mostly temporary, and therefore are not sustainable. There are limitations and lack of effective implementation of the existing law in ensuring safe food. In addition, although the relevant departments of several ministries are engaged in administrative and supervisory activities to ensure safe food, there is a lack of coordination and communication between them due to the absence of a unified institutional structure. On the other hand, the lack of internal monitoring and accountability, along with the institutional limitations of the supervisory institutions, is noticeable. Due to these limitations, is creating a huge threat to the health and safety of the common citizen. A set of recommendations have been presented in this study to achieve positive changes in this situation. It also contributes insights to navigate the complexities of stakeholder involvement in food security policy, informing the development of more effective, inclusive policies for enduring and sustainable food security in Bangladesh.